Technology, society and sustainability : selected concepts, issues and cases - Zacher, Lech (Springer, 2017)
This collection is a multidisciplinary and multicultural contribution to the current sustainability discourse. It is focused on two main dimensions of our world: complexity and diversity. Desirable and urgent transition of socio-technological systems toward a sustainability trajectory of development requires a better understanding of technological trends and social transformations. General advancement of technology does not produce identical changes in various societies, differentiated economically and culturally. Moreover, the abilities to approach sustainable development change over time and space. As a result there is a constant need for continuing research, analyses, and discussions concerning changing contexts and adequacy of strategies and policies. Authors from twelve countries and of different academic and cultural settings present their insights, analyses and recommendations. The collection is focused both on contexts and on activities leading to sustainable trajectories in various domains of economy and social life. Continuing research and discussion is needed to better understand these challenges and to prepare the appropriate strategies and solutions. Development of socio-technological systems is nowadays very complex; moreover, the world we live in is extremely diverse. Therefore, sustainability discourse must be ongoing, introducing new ideas, concepts, theories, evidence and experience by various parties--academics, professionals, and practitioners.